Concept paper on novel radio frequency resistive switches - Kiazadeh, Asal (2024)
Funding Information: This work has been (partially) supported by the Smart Networks and Services Joint Undertaking (SNS JU) under the European Union’s Horizon Europe research and innovation programme under Grant Agreement No 101097101, including top-up funding by UK Research and Innovation (UKRI) under the UK government’s Horizon Europe funding guarantee. Furthermore, this work was financed by national funds from FCT - Fundação para a Ciência e a Tecnologia, I.P., in the scope of the projects LA/P/0037/2020, UIDP/50025/2020 and UIDB/50025/2020 of the Associate Laboratory Institute of Nanos-tructures, Nanomodelling and Nanofabrication – i3N and by the grants 2021.03386.CEECIND and CEECINST/00102/2018. Publisher Copyright: © 2023 Owner/Author.